The Rural Sport Event—The Atmosphere from the Participants’ Perspective - Luiza Ossowska; Dariusz Kloskowski; Dorota Janiszewska (Tourism and Hospitality)
Rural sport events can play an important role in the sustainable development of rural areas, and bring various benefits. The atmosphere of a rural sport event covers the character and feeling of a place and situation. The aim of this article is to assess the impact of rural sport event atmosphere on participants. Research was conducted using the IPA method (Importance–Performance Analysis). On 22 January 2022, 127 respondents assessed the atmosphere of a running sport event—before the run defining “importance”, and after the run defining “performance” (a survey questionnaire with a five-point Likert scale was used). The research covers three groups of factors: event organization (rules and safety, management and hosting, sport competition class), relationships between participants (integration, sharing passion, ability to compete), and event place (attractiveness of the area, attractiveness of the sport competition place, and the will to return to the place). For both the “importance” and “performance” scales, the examined factors received high values (from 3.80 to 4.77). The conducted research shows that atmosphere is a key element when building a rural sport event. Satisfaction with a running event has a positive impact on the perception of the event and its atmospheric components.